PENYULUHAN KETAHANAN PENGAN LOKAL PADA MASA PANDEMI DI DESA GURUAPIN KAB HALMAHERA SELATAN - Aziz Hasyim; Musdar Muhammad (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of the service is to improve food security in the guraping village community, by mandating the land of the yard of the house and the land of guraping village boarding house, building community awareness, village government and housewives to meet food needs during the pandemic. The methods applied to Community Service are the Focus Group Discussion (FGD) method and Training and monitoring; As for the results of devotion; Guruaping village grows local food problems faced, namely related to water shortages, there are also results of food products that do not know the market. BUMDes has been inactive to increase community efforts